Potent and Selective Fluoroketone Inhibitors of Group VIA Calcium-Independent Phospholipase A2 - Kokotos, George; Hsu, Yuan-Hao; Burke, John E.; Baskakis, Constantinos; Kokotos, Christoforos G.; Magrioti, Victoria; Dennis, Edward A. (Journal of Medicinal Chemistry, 2010)
Group VIA calcium-independent phospholipase A2 (GVIA iPLA2) has recently emerged as a novel pharmaceutical target. We have now explored the structure−activity relationship between fluoroketones and GVIA iPLA2 inhibition. The presence of a naphthyl group proved to be of paramount importance. 1,1,1-Trifluoro-6-(naphthalen-2-yl)hexan-2-one (FKGK18) is the most potent inhibitor of GVIA iPLA2 (XI(50) = 0.0002) ever reported. Being 195 and >455 times more potent for GVIA iPLA2 than for GIVA cPLA2 and GV sPLA2, respectively, makes it a valuable tool to explore the role of GVIA iPLA2 in cells and in vivo models. 1,1,1,2,2,3,3-Heptafluoro-8-(naphthalene-2-yl)octan-4-one inhibited GVIA iPLA2 with a XI(50) value of 0.001 while inhibiting the other intracellular GIVA cPLA2 and GV sPLA2 at least 90 times less potently. Hexa- and octafluoro ketones were also found to be potent inhibitors of GVIA iPLA2; however, they are not selective.